2022
DOI: 10.1038/s41598-022-12524-7
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of salicylic acid phenylethyl ester (SAPE) and its implication in immunomodulatory and anticancer roles

Abstract: Salicylic acid phenylethyl ester (SAPE) was synthesized by Zn(OTf)2-catalyzed selective esterification of salicylic acid and phenylethyl alcohol and studied for its role as an immunomodulatory and anticancer agent. Low toxicity and favorable physical, Lipinski-type, and solubility properties were elucidated by ADME-tox studies. Molecular docking of SAPE against COX-2 revealed favorable MolDockscore, rerank score, interaction energy, internal pose energy, and hydrogen bonding as compared to ibuprofen and indome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Moreover, the introduction of the lactone to a compound structure increases anticancer activity [ 68 , 69 ]. Additionally, the introduction of bromine improves lipophilicity and biomedical application [ 70 ], and compound esterification increases water solubility [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the introduction of the lactone to a compound structure increases anticancer activity [ 68 , 69 ]. Additionally, the introduction of bromine improves lipophilicity and biomedical application [ 70 ], and compound esterification increases water solubility [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…8 Sialicacid is primarily made up of glycoproteins and glycol lipids found at the membrane of cells. 9 In the acute phase of a reaction, sialic acid is considered a biomarker . 18 The negative charge on renal basement membrane also controlled by sialic acid, so sialic acid consider as one of main regulator of membrane permeability.…”
Section: Discussionmentioning
confidence: 99%
“…7 As a cofactor, sialic acid is mainly active during acute stages of inflammation or injury, and it acts primarily on cell receptors as a cofactor. 8,9 In the cell membrane, glycoproteins and glycol lipids, which form sialic acid, make up a significant portion of the structure. 10 Endothelial and vascular permeability of sialic acid is controlled by the molecular composition of sialic acid.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Salicylic acid (SA), as the FDA approved antiinflammatory drug, is the functional ingredient of aspirin, which has been reported to restrain the activity of the COX-2/ PGE 2 axis. 9,10,15 Given its side effects limiting potential application in tumor therapy, nanoparticles-based drug delivery systems may be developed for the selective delivery of SA to tumor sites. Nanotherapy platforms have been particularly promising for tumor therapy over two decades.…”
mentioning
confidence: 99%
“…Several previous studies have revealed the antitumor effect of COX-2/PGE 2 inhibitors to boost antitumor immunotherapy at high-dose administration. ,, However, one lethal vulnerability is that oral high-dose administration of COX-2/PGE 2 inhibitors can cause gastrointestinal bleeding and cardiac events. , Salicylic acid (SA), as the FDA approved anti-inflammatory drug, is the functional ingredient of aspirin, which has been reported to restrain the activity of the COX-2/PGE 2 axis. ,, Given its side effects limiting potential application in tumor therapy, nanoparticles-based drug delivery systems may be developed for the selective delivery of SA to tumor sites. Nanotherapy platforms have been particularly promising for tumor therapy over two decades.…”
mentioning
confidence: 99%